Distribution of Risk Factors in Male and Female Primary Health Care Patients with Osteoarthritis in Albania - Hoxha, Fatos (Med Arch, 2015)
AIM: We aimed to describe the distribution of the main risk factors among primary health care users diagnosed with osteoarthritis in Albania, a post-communist country in South Eastern Europe. METHODS: Our study involved all individuals who were diagnosed with osteoarthritis over a two-year period (January 2013 – December 2014) in several primary health care centers in Tirana, the Albanian capital. On the whole, during this two-year period, 1179 adult individuals were diagnosed with osteoarthritis (521 men aged 60.1±10.6 years and 658 women aged 58.1±9.6 years). According to the criteria of the American College of Rheumatology, the diagnosis of osteoarthritis was based on the history of the disease, physical examination, laboratory findings and radiological findings. Binary logistic regression was used to assess the sex-differences regarding the major risk factors among individuals diagnosed with osteoarthritis. RESULTS: In multivariable-adjusted logistic regression models, female gender was inversely associated with smoking (OR=0.39, 95%CI=0.27-0.56), alcohol intake (OR=0.08, 95%CI=0.06-0.10), overweight but not obesity (OR=0.65, 95%CI=0.46-0.91 and OR=0.74, 95%CI=0.46-1.18, respectively), weight lifting (OR=0.38, 95%CI=0.22-0.66) and heavy physical exercise (OR=0.69, 95%CI=0.46-1.03). Conversely, female gender was positively related to genetic factors (OR=2.17, 95%CI=1.55-3.04) and preexisting inflammatory diseases (OR=1.53, 95%CI=0.93-2.53). CONCLUSION: This study offers useful evidence about the distribution of the main risk factors for osteoarthritis in adult individuals diagnosed with osteoarthritis in Albania. This information may support health professionals and decision-makers in Albania for evidence-based health planning and policy formulation in order to control the toll of osteoarthritis in this transitional society.